2014
DOI: 10.1371/journal.pone.0107945
|View full text |Cite
|
Sign up to set email alerts
|

Rosa26 Locus Supports Tissue-Specific Promoter Driving Transgene Expression Specifically in Pig

Abstract: Genetically modified pigs have become a popular model system in fundamental research, agricultural and biomedical applications. However, random integration often result in unstable expression of transgene and unpredictable phenotypes. The Rosa26 locus has been widely used to produce genetic modified animals with high and consistent expressing of transgene in mouse, human and rat, as it can be targeted efficiently and is not subject to gene-silencing effects. Recently, the first case of reporter gene targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…The sequence of the pig ROSA26 (pROSA26) locus has been completely characterized, and the pRosa26 promoter has been identified 8 . This porcine endogenous promoter is suitable for driving exogenous gene expression in a high and stable manner by avoiding DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of the pig ROSA26 (pROSA26) locus has been completely characterized, and the pRosa26 promoter has been identified 8 . This porcine endogenous promoter is suitable for driving exogenous gene expression in a high and stable manner by avoiding DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, genetically modified pigs were generated either via random integration 5 or conventional homologous recombination. 6 However, random insertions often cause variable expression levels of the transgene, 7 whereas conventional HR targeting is extremely inefficient, 8 and the insertion of antibiotic selection cassettes has raised concern about their clinical prospects.…”
Section: Introductionmentioning
confidence: 99%
“…The most preferred integration site used for transgene insertionis the Rosa26 locus in mice. As in mice, the human and rat Rosa26 loci were identified and successfully targeted using traditional HR 13 . There have reported that knock-in of a long DNA fragment via homology-independent DNA repair can be achieved in zebrafish using the CRISPR/Cas9 system.…”
mentioning
confidence: 99%